Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, Dan Sanksi Pajak Kendaraan Bermotor Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Provinsi Aceh - Lilis Maryasih; Neza Aulia (Department of Accounting, Faculty of Economics & Business, 2022)
This study aims to determine the effect of tax knowledge, taxpayer awareness, and motor vehicle taxpayers sanction on compliance with motor vehicle taxpayers (PKB) in Aceh Province. The population in this study were motor vehicle taxpayers who were registered at samsat office in Aceh Province. The data used are primary data by distributing questionnaires with google form. The method for determining non-probability sampling with Accidental Sampling techniques. Based on the Slovin formula obtained a sample of 100 taxpayers. Data analysis method uses validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing and determination test.The result of hypothesis testing indicates that tax knowledge has a positive effect on motor vehicle tax compliance. Taxpayers awareness has a positive effect on motor vehicle tax compliance. Motor vehicle taxpayers sanction has a positive effect on motor vehicle tax compliance. Adjusted R Square value (R2) is 0,521 or 52,1%. So R2 of 52,1% is influenced by the variables used in this study while the remaining 47,9% is influenced by variables outside the research, for example public service accountability, fiscal service, and SAMSAT drive thru system.